2007
DOI: 10.1007/s10165-006-0555-6
|View full text |Cite
|
Sign up to set email alerts
|

Inositol 1,4,5-trisphosphate receptors are autoantibody target antigens in patients with Sjögren's syndrome and other systemic rheumatic diseases

Abstract: IP(3)R2 and IP(3)R3 double knock-out mice present with exocrine dysfunctions such as secretion deficits of saliva and pancreatic juice. Therefore, we investigated whether the presence of antibodies to IP(3)Rs could be found in patients with Sjögren's syndrome, and the location of the epitopes. Subjects included 35 primary Sjögren's syndrome, 39 secondary Sjögren's syndrome, 144 rheumatoid arthritis, and 96 other connective tissue disease patients. As controls, 33 healthy subjects were included. Immunoblot was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
1
8
0
1
Order By: Relevance
“…While there are some discrepancies in the reported findings 39 40 41 , it is feasible to hypothesize that if there were high levels of circulating anti-M3R in vivo in the vicinity of the receptors in the gland, it could dampen the cellular response to neurotransmitter stimulation. Additionally, antibodies to IP3R have also been detected in sera from primary Sjögren’s 17 of 35 (48.6%), secondary Sjögren’s 13 of 39 (33%), and rheumatoid arthritis 34 of 124 (27.4%) 42 . However, it is unclear whether autoantibodies can induce permanent effects on the acinar cells which would lead to dampening of their response to (CCh) in vitro , as seen in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…While there are some discrepancies in the reported findings 39 40 41 , it is feasible to hypothesize that if there were high levels of circulating anti-M3R in vivo in the vicinity of the receptors in the gland, it could dampen the cellular response to neurotransmitter stimulation. Additionally, antibodies to IP3R have also been detected in sera from primary Sjögren’s 17 of 35 (48.6%), secondary Sjögren’s 13 of 39 (33%), and rheumatoid arthritis 34 of 124 (27.4%) 42 . However, it is unclear whether autoantibodies can induce permanent effects on the acinar cells which would lead to dampening of their response to (CCh) in vitro , as seen in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…IP 3 R2‐R3 KO mice show symptoms of dry mouth and dry eye (unpublished observations) that are similar to the characteristics of Sjogren’s syndrome. An analysis of sera from patients with Sjogren’s syndrome revealed that anti‐IP 3 R antibodies were present at a rate of close to 50%, as detected using western blotting (Miyachi et al. 2007).…”
Section: Role Of Ip3r2 3 In Exocrine Secretionmentioning
confidence: 99%
“…2007). Antibodies against IP 3 Rs are also present in more than 30% of sera samples from patients with systemic rheumatic disease (Miyachi et al. 2007), suggesting that IP 3 Rs play an important role in exocrine secretion and that immunoscreening could be used as a diagnostic tool for Sjogren’s syndrome and systemic rheumatic diseases.…”
Section: Role Of Ip3r2 3 In Exocrine Secretionmentioning
confidence: 99%
“…Because in a previous study 6 it was shown that 48.6% (17/35) of patients with primary Sjögren syndrome harbored antibodies against IP3R1, we assayed 45 patients with primary Sjögren syndrome with our specific CBA; they were all negative. This discrepancy is likely attributed to different specificity and sensitivity of the methods used or possibly to the difference of diagnostic criteria used in defining disease among the examined patients.…”
Section: Resultsmentioning
confidence: 99%